Findings of metal translocation to herbivores in territories affected by contamination from industrial complexes, Chile - Meza-Ramírez, Verónica; Espinoza-Ortiz, Ximena; Castillo-Allaria, Javier; Espinoza-Brito, Luis; Ramos-Hernández, Maribel; Cuminao-Rojo, Clorinda; Torres-Espinoza, María Paz (Brawijaya University, 2025)
Heavy metals in high concentrations from industrial areas are deposited in the soil and, as a result of ecosystem interrelationships, enter and are harmful to living beings. To determine if there is translocation of metals from the soil to herbivorous animals, the team of the Laboratory of Learning, Technology and Democratization in Soils and Communities (LAPTES) conducted a first exploratory study and then a complementary study of the translocation of heavy metals such as Copper (Cu), Arsenic (As), Cadmium (Cd) and Lead (Pb) in localities near the Ventanas Industrial Complex (CIV). Fecal samples were collected from different points of the La Greda School, using standard methods for the determination of heavy metals in certified laboratories. The results were analyzed using correlation coefficients, Spearman correlation matrix, and descriptive statistics. It was shown that there was a correlation between the presence of metals in the soil and the feces of herbivorous animals. It is concluded that there would be a risk in the hunting and consumption of local lagomorphs on contaminated soils, affecting food security, making it necessary to strengthen environmental education through soil remediation in contaminated territories, considering the active participation of the communities.